The reliability and validity of rehabilitation set of the international classification of functioning, disability, and health in assessing Chinese tumor patients - Qianqian Sun; Zhi Zou; Wei Guo; Rui Li; Suchen Zhao; Hao Yu; Xiaoguang Yang; Zeyang Yu; Luwen Zhang; Hongyu Zhai; Tiebin Yan (PLoS ONE, 2026)
Background and aim There is currently no comprehensive scale suitable for assessing the rehabilitation progress of Chinese tumor patients. This study aimed to evaluate the psychometric properties of the Rehabilitation Set of the International Classification of Functioning, Disability, and Health for that purpose. Methods The Chinese version of the International Classification of Functioning, Disability, and Health’s Rehabilitation Set (ICF-RS) was used by trained health professionals to assess 1055 Chinese tumor patients. The internal consistency of the responses was assessed in terms of Cronbach’s alpha coefficient. Construct validity was explored through factor analysis. Test-retest reliability, inter-rater reliability, and criterion validity were evaluated using a subset of 121 patients. Criterion validity was quantified by correlating the scores with those generated using the Hospital Anxiety and Depression scale (HADS), the Eastern Cooperative Oncology Group (ECOG) performance status evaluation and the modified Barthel Index (MBI). Results The Cronbach’s alpha for the rehabilitation set’s scores was 0.87, indicating good internal consistency. The test-retest reliability analysis showed that most categories had an intraclass correlation coefficient in excess of 0.75, suggesting good reliability when the rehabilitation set is applied with tumor patients. Inter-rater reliability also demonstrated intraclass correlation greater than 0.75 for most categories. Construct validity was supported by the finding that 18 categories had factor loadings exceeding 0.40. After removing categories with lower factor loadings, the cumulative variance explained increased to 44.6% for the Activity and Participation component and 57.3% for the Body Functions component. Criterion validity was supported by significant associations with established instruments. Specifically, 66.7% (20/30) of the ICF-RS categories correlated significantly with the MBI, with effect sizes (r) ranging from 0.19 to 0.52 (p < 0.05). In contrast, only 10% (3/30) of categories demonstrated significant correlations with the ECOG ratings (ρ = 0.21–0.22, p < 0.05). Furthermore, categories related to emotional functions and psychological demands showed significant correlations with the HADS, with moderate effect sizes (ρ = 0.37–0.41, p < 0.001). Conclusions The Chinese version of the ICF-RS exhibits promising psychometric properties in tumor patients, providing preliminary evidence for its clinical application. It demonstrates good internal consistency, high test-retest reliability and reliable inter-rater consistency. The moderate correlation with MBI ratings and HADS scale scores, along with the distinct factors identified through factor analysis, further supports the instrument’s validity and utility when applied to this population. The data confirm that the ICF-RS is a reliable tool for assessing tumor patients’ functioning and disability. However, the construct validity results recommend further work before the instrument is widely used with tumor patients.